Effects Of Endurance Training On Expression Endothelial Nitric Oxide Synthase And Nitric Oxide Production In Human Placenta (2013)
To determine the effects of combined aerobic and resistance exercise training during the second half of pregnancy on endothelial NOS expression (eNOS), nitric oxide (NO) production and oxygen metabolism in human placenta.